Ethical standards in arbitration practice in Indonesia: Challenges and strengthening of oversight - Hayati, Vivi; Iqbal, Muhammad; Masthura, Natasya; Anwar, Saiful; Hasmiyati, Cut (Jurnal Geuthèë: Penelitian Multidisiplin, 2025)
Arbitration is an increasingly developing dispute resolution mechanism in Indonesia, particularly in the business and trade sectors. To ensure its credibility and effectiveness, ethical standards in arbitration practice must be strictly enforced. This study analyzes the implementation of ethical standards in arbitration in Indonesia, the challenges faced, and solutions for strengthening oversight and enforcement mechanisms. Some key challenges identified include conflicts of interest among arbitrators, lack of transparency in arbitration processes, and weak regulations and sanction mechanisms for ethical violations. Using a normative-empirical legal research method, this study highlights the importance of regulatory reforms, enhancing the role of supervisory institutions, and utilizing technology in the arbitration system. The implementation of digital registration systems, blockchain, and artificial intelligence (AI) can improve transparency and accountability in arbitration in Indonesia. With stricter oversight strategies, arbitration is expected to become a fairer, more efficient, and more credible dispute resolution mechanism.